Exploiting the Genetic Diversity of Maize Using a Combined Metabolomic, Enzyme Activity Profiling, and Metabolic Modeling Approach to Link Leaf Physiology to Kernel Yield. Issue 5 (10th April 2017) - Cañas, Rafael A.; Yesbergenova-Cuny, Zhazira; Simons, Margaret; Chardon, Fabien; Armengaud, Patrick; Quilleré, Isabelle; Cukier, Caroline; Gibon, Yves; Limami, Anis M.; Nicolas, Stéphane; Brulé, Lenaïg; Lea, Peter J.; et al.
Abstract : A metabolomic, biochemical, fluxomic, and metabolic modeling approach developed using 19 genetically distant maize lines links leaf physiology to kernel yield. Abstract: A combined metabolomic, biochemical, fluxomic, and metabolic modeling approach was developed using 19 genetically distant maize ( Zea mays ) lines from Europe and America. Considerable differences were detected between the lines when leaf metabolic profiles and activities of the main enzymes involved in primary metabolism were compared. During grain filling, the leaf metabolic composition appeared to be a reliable marker, allowing a classification matching the genetic diversity of the lines. During the same period, there was a significant correlation between the genetic distance of the lines and the activities of enzymes involved in carbon metabolism, notably glycolysis. Although large differences were observed in terms of leaf metabolic fluxes, these variations were not tightly linked to the genome structure of the lines. Both correlation studies and metabolic network analyses allowed the description of a maize ideotype with a high grain yield potential. Such an ideotype is characterized by low accumulation of soluble amino acids and carbohydrates in the leaves and high activity of enzymes involved in the C4 photosynthetic pathway and in the biosynthesis of amino acids derived from glutamate. Chlorogenates appear to be important markers that can be used to select for maize lines that produce larger kernels.